2001
DOI: 10.1111/j.1751-0813.2001.tb14571.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulosa cell tumour in two speyed bitches

Abstract: Granulosa cell tumours are uncommon ovarian tumours in the bitch and are rare in speyed bitches. This case report describes two cases of granulosa cell tumour in bitches that were speyed at less than 1-year-of-age. Both animals presented with persistent vulval bleeding. Although the majority of granulosa cell tumours are large enough to be palpated by the time of presentation, both tumours were relatively small. Granulosa cell tumour is a possible complication of incomplete ovarian excision at the time of ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 10 publications
2
32
0
1
Order By: Relevance
“…Interestingly, development of granulosa cell tumors has been reported in spayed bitches as in the present case [20,26]. One of them showed a predominance of lobules of luteallike cells accompanied by granulosa cells proliferating in a Sertoli cell pattern [26].…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Interestingly, development of granulosa cell tumors has been reported in spayed bitches as in the present case [20,26]. One of them showed a predominance of lobules of luteallike cells accompanied by granulosa cells proliferating in a Sertoli cell pattern [26].…”
mentioning
confidence: 68%
“…The present case exhibited abnormal vaginal bleeding that is known to be the most frequent clinical manifestation of granulosa cell tumors and luteomas [26,[28][29][30]. Interestingly, development of granulosa cell tumors has been reported in spayed bitches as in the present case [20,26]. One of them showed a predominance of lobules of luteallike cells accompanied by granulosa cells proliferating in a Sertoli cell pattern [26].…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…This type of tumour is the second most frequent ovarian tumour in bitches, has multifactorial aetiology and 20% of cases exhibit metastasis. Sivacolundhu et al (2001) reported that GCTs are uncommon in bitches, and are rare in spayed bitches. In this last case, similarly to the case reported here, it can be suggested that the granulosa cell tumour was associated with the incomplete ovarian excision at the time of ovariohysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, surgical intervention can lead to disease associated with reproductive tissue which was properly removed. Granulosa cell tumours, pyometra, mammary tumours and other diseases associated with the release of steroid hormones from ovary remnants have all been linked with improper removal of reproductive tissue (Sivacolundhu et al 2001;Ragni 2005;Christensen et al 2013). Some reports have described the presence of uterine and ovarian remnants in bitches after ovariohysterectomy (Ball et al 2010), usually linked to pyometra.…”
mentioning
confidence: 99%